Analyzing Tobin’s Q Ratio of Banking Industry of Bangladesh: A Comprehensive Guideline for Investors - Ali, Md. Rostam; Mahmud, Md. Shahed; Lima, Reshma Pervin (Asian Business Review, 2016)
Due to the share market crash in 2010-2011, the investors have lost confidence regarding the share market till now. Therefore, this study is an endeavor to giveaway to rethink about the share market of Bangladesh and to increase the confidence of the investors. For that, Tobin’s Q ratio used to analyze the share market in this study. Tobin’s Q represents the ratio of the market value of a firm’s share capital to the replacement cost of the firm’s share capital. Tobin’s Q is greater than one means stock is overvalued. Tobin’s Q is less than one means stock is undervalued. Again, Tobin’s Q is equal to one means stock is fairly valued. The study found that, the value of Tobin’s Q of the all sampling banks is gradually decreasing means moving the value of the stock from overvalued to undervalue. The value of Tobin’s Q of the all sampling banks is less than one in the year 2014 except Dutch Bangla Bank Limited (DBBL). The average value of Tobin’s Q of the banking industry is also decreasing and the average value of Tobin’s Q of the banking industry is less than one in the year 2014. Thus, the average stock value of the banking industry is moving from overvalued to undervalue gradually. Again, the value of Tobin’s Q of all sampling banks fell down drastically from the year 2010 to the year 2011 as share market has been crashed in those years. As a result, the average value of Tobin’s Q of banking industry also fell down drastically from the year 2010 to the year 2011. Therefore, the value of the share slopes down drastically from the year 2010 to the year 2011.